A study on the adequacy of Kota Kinabalu Sabah's solid waste management policy / Haidy Henry Dusim - Dusim, Haidy Henry (Universiti Teknologi MARA, 2021)
A country with an adequate solid waste management policy should theoretically be able to better address its solid waste issues. Regrettably, not every country, particularly those in developing countries, has a solid waste management policy that is adequate. As a result, the majority of developing countries continue to struggle with solid waste issues. The effectiveness of solid waste management policies is investigated in this study. Due to ongoing solid waste management issues in Kota Kinabalu, Sabah, the city of Kota Kinabalu was chosen as a case study to further investigate the topic of policy inadequacy. The data for this study was collected and analysed using a qualitative method. According to the findings of the study, Kota Kinabalu's current solid waste management policy is still inadequate. This is because Kota Kinabalu's current solid waste management policy is still insufficient. As a result, the long-term viability of solid waste management in Kota Kinabalu, Sabah, is undermined. As a result, a more comprehensive solid waste management strategy is required.